2011
DOI: 10.4314/ijbcs.v4i6.64908
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of captopril and allylmercaptocaptopril in the maintenance of oxidative-antioxidative equilibrium and attenuation of selenite-induced cataract in rats

Abstract: The present study was undertaken to investigate the comparative efficacy of captopril (CP) and allylmercaptocaptopril (AMC) supplementation following selenite exposure with respect to oxidant-antioxidant equilibrium and prevents cataract formation in rat pups. Forty Wistar-albino rat pups were equally divided into 4 groups. In Group I; only subcutaneous (s.c) saline was injected. In Group II; single dose of sodium selenite (19 µM/kg body weight, s.c) was injected on postpartum day 10. One day before the seleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
2
0
0
Order By: Relevance
“…As an indicator of lipid peroxidation, the level of MDA, was higher in the Se group than in the control groups (p < .05), which is in line with the selenite mechanism in cataract formation mentioned above. The results of this study corroborate earlier studies which reported higher MDA levels in lens tissues of selenite-induced cataract subjects (Lakshmi & Sharma, 2010;Yang et al, 2013). Additionally, in our study, MDA content was significantly lower in the Se + P group than in the Se group (p < .05), suggesting that administration of pomegranate peel extract possibly inhibited the disruption of lenticular membrane lipids by scavenging the highly reactive hydroxyl and peroxyl radicals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As an indicator of lipid peroxidation, the level of MDA, was higher in the Se group than in the control groups (p < .05), which is in line with the selenite mechanism in cataract formation mentioned above. The results of this study corroborate earlier studies which reported higher MDA levels in lens tissues of selenite-induced cataract subjects (Lakshmi & Sharma, 2010;Yang et al, 2013). Additionally, in our study, MDA content was significantly lower in the Se + P group than in the Se group (p < .05), suggesting that administration of pomegranate peel extract possibly inhibited the disruption of lenticular membrane lipids by scavenging the highly reactive hydroxyl and peroxyl radicals.…”
Section: Discussionsupporting
confidence: 92%
“…However, preventive administration of PPE with antioxidant activity (Guo et al, 2003) did delay the occurrence of fully developed cataract. In line with this research, other studies have reported a delay in the occurrence of selenite-induced fully developed cataracts using compounds with antioxidant activity such as α-glucosyl hesperidin (Nakazawa et al, 2020), rosmarinic acid (Tsai et al, 2019), caffeic acid phenethyl ester (Doganay et al, 2002), captopril and allylmercaptocaptopril (Lakshmi & Sharma, 2010), apricots (Doganay et al, 2013), and melatonin as an endogenous antioxidant (Yağci et al, 2006). As shown in Table 1, increased SOD, CAT, and GPx activity and reduced GSH levels were observed in the lens tissues of the Se group compared to the control group, which was consistent with the results of Shearer et al (1997).…”
Section: Discussionsupporting
confidence: 79%